The Effectiveness of Extract Basil Leaves on Motility and Morphology of Spermatozoa Mice Exposed with Cigarette Smoke - Bagas Setiawan Ihsan Zaini; Izki Masyaqqoni Pujiana; Evi Octavia Djamaludin; Hotimah Masdan Salim (Biomolecular and Health Science Journal, 2020)
Introduction: The incidence of infertility is still a problem in the world, including Indonesia (21.3%), and throughout Asia. Fertility in men is strongly influenced by several factors, one of them is smoking. Smoking can increase ROS, reduce antioxidants in semen, cause DNA damage, and morphological abnormalities of spermatozoa. Basil contains flavonoids which are rich in antioxidants, boron, and zinc to stimulate androgen hormones.Methods: This research used eight weeks old Mus musculus, exposed with smoke of 20 cigarettes/day and was administered of extract basil leaves (Ocimum sanctum L.) in dose dependency (100 mg/kg, 200mg/kg, and 300mg/kg) for 4 weeks. We examined the motility and morphology of spermatozoa by microscope. This research consisted of 5 groups. In CS-, CSBL-2 and CSBL-3, it showed that the spermatozoa motility was more progressive than CS+ and CSBL-1.Results: The morphology of spermatozoa in CS+ and CS- found different results with a significance value of 0.10 (p < 0.05) but the results of CSBL- 1, CSBL-2, and CSBL-3 were not significantly different from CS- and CS+ (p > 0.05).Conclusion: There was an effect of giving basil leaves to increase motility and improvement of the morphology of spermatozoa that had been exposed to cigarette smoke especially in dose 300 mg/kgBB, but it was not significant.